ALIENASI RELIGIUS DALAM FILM PEREMPUAN BERKALUNG SORBAN - Danial Hidayatullah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2011)
In Western literary tradition, alienation is a common theme. This theme has been identified since the Shakespearean era. Yet, in Indonesian literary tradition alienation is a novelty. This paper aims at analyzing the emergence as well as the significance of this theme in the Indonesian context. In Western context, alienation occurs within the absence of God or within the materialistic society while in Indonesian context, in this case in Perempuan Berkalung Sorban, it occurs in a strong religious atmosphere. The main character, Anisa experiences alienation caused by the interpretation of religion by patriarchal society. The psychological conflict between religious rules and free will is so intense that the main character is trapped in a deep confusion. Therefore this research is intended to examine how the religious alienation can be explained in Indonesian context. This paper provides the explanation on how this movie—Perempuan Berkalung Sorban—fits into the category of the movie that criticizes religion. The emergence of a new theme in a popular culture mainstream can be seen as a new awareness in Indonesian culture.